Stability of vitamin E and or K in cooking oil during the frying process - Nabila, Talitha Shanda; Ati, Tiara Mustika; Nursafitri, Rifa Ayu; Padilah, Fikri Dwi; Maerani, Maerani; Faturohman, Hadi Yusuf (Nutrition Scientific Journal, 2024)
Cooking oil is the main ingredient in food processing that acts as a heat transfer medium, energy source, and solvent for vitamins A, D, E, and K. However, the frying process can affect the stability of vitamins, especially vitamins E and K, contained in the oil. This article aims to examine the stability of vitamins E and K in vegetable oil at high temperatures and how much remains after the frying process, as well as factors that affect degradation such as temperature, time, and oxygen exposure. Through a literature review, it was found that high temperatures and long heating can accelerate the damage to vitamins E and K, which is indicated by an increase in the peroxide number and changes in oil quality. Efforts to reduce degradation include regulating frying temperature and duration, avoiding exposure to oxygen and light, using additional antioxidants, and using chelating agents.